‘That Is Actually Bollocks’: 20 Propaganda Horrors From 20 Years of Media Lens - Part 1 (Media Lens, 2021)
After 20 years of Media Lens, it seems only natural that we should look back in gratitude at the support we’ve received. In response to one of our early pieces, a kindly columnist at the Observer commented: ‘Dear David,‘Thank you very much for sending me a copy of your piece, which strikes me as